Efecto del vecindario sobre la remoción de frutos: predicciones teóricas con un muérdago en un ecosistema urbano - Ruales Abrigo, Jonathan Agustin (2024)
In the academic sphere, there are few studies dedicated to making theoretical predictions about plant species in urban ecosystems. Therefore, an analysis has been carried out on how the size of the available fruit harvest of mistletoe (Phoradendron nervosum) in an urban environment can influence competition or facilitation among plants, mediated by frugivorous seed-dispersing birds, specifically in the city of Loja. P. nervosum is a hemiparasitic plant, which means it obtains the nutrients it needs from a host, but it can also serve as shelter and food for other species. To conduct the study, three areas were selected in the urban environment of the city, where five willow trees (Salix humboldtiana) infested with mistletoe were identified in each area. Circular areas with a distance of 30 meters around the focal trees were delimited, considering them as "fruit neighborhoods." During a period of 45 minutes, interactions between birds and mistletoe on the selected trees were observed. Mistletoe samples were collected in three different sizes (large, medium, and small), with five specimens per size, and the number of fruits was counted to calculate an average. The results showed that the variables of visitation rates and fruit removal were positively related to the size of the P. nervosum harvest in the context of neighborhoods. This demonstrates that the neighborhood has a significant effect on the removal of P. nervosum fruits in an urban environment. It is suggested that the fruit removal rate increases (i.e., is facilitated) as the density of neighboring conspecific mistletoe fruits increases.